Nivolumab for Metastatic Urothelial Cancer in a Renal Allograft Recipient With Subsequent Graft Rejection and Treatment Complete Remission: A Case Report - Chen, Didi; Wu, Xinyi; Xie, Congying (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) expanded the therapeutic options for several cancers. However, whether some special groups of patients including those with organ transplantation can receive ICIs remains unclear. In this report we presented an interesting case. A 54-year-old woman underwent kidney transplantation, developed metastasis 7 years after operation of the bladder tumor. Her disease progressed after chemotherapy and radiothrapy. Anti-PD-1 immunotherapy was then considered. After two cycles of nivolumab immunotherapy, the patient’s renal function declined rapidly. Acute allograft rejection was considered. There was no significant decrease in creatinine after glucocorticoid pulse therapy. Third course of nivolumab was given, and regularly hemodialysis was simultaneously conducted. Two weeks later, the patient showed left abdominal pain. CT scan revealed a reduction in tumor burden, while enlarged volume of kidney graft. Immunotherapy stopped. Two months after the third course, CT demonstrated a complete remission to immunotherapy. 23 months after the third course, CT showed that the swelling transplanted kidney was smaller than previous, and no recurrence was observed.